1998
DOI: 10.1007/pl00007024
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Induces Gums and Stimulates Anthocyanin Accumulation in Peach Shoots

Abstract: The effect of methyl jasmonate (JA-Me) on the induction of gum was studied in relation to the action of ethylene in peach (Prunus persica Batsch cv. Benishimizu) shoots. JA-Me applied at concentrations of 0.1-2.5% (w/w) in lanolin paste to current growing or older shoots substantially induced gums 3 days after treatment. The amount of gums exuded increased depending on the dose of JA-Me. Ethephon (2-chloroethylphosphonic acid) at 1 or 2% (w/w) in lanolin induced gum and strongly enhanced the promoting effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…MeJA has been shown to enhance anthocyanin accumulation in soybean seedlings (Franceschi and Grimes, 1991), peach shoots (Saniewski et al, 1998), and apple fruits (Kondo et al, 2001). Kondo et al (2001) showed that jasmonates effectively stimulated anthocyanin biosynthesis and that such effect was independent of ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…MeJA has been shown to enhance anthocyanin accumulation in soybean seedlings (Franceschi and Grimes, 1991), peach shoots (Saniewski et al, 1998), and apple fruits (Kondo et al, 2001). Kondo et al (2001) showed that jasmonates effectively stimulated anthocyanin biosynthesis and that such effect was independent of ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…As was previously published, MJ has a stimulatory effect on anthocyanins accumulation in hypocotyls of lightgrown soybean seedlings (Franceschi and Grimes 1991), in shoots of wild Arabidopsis thaliana (Feys et al 1994), in detached corollas of Petunia (Tamari et al 1995), in the stem and leaves of tulips (Saniewski et al 1998a), in peach shoots (Saniewski et al 1998b), in cell cultures of Vaccinium pahalae (Fang et al 1999), in apple fruits (Kondo et al 2001), in suspension cultures of Vitis vinifera (Zhang et al 2002), and in shoots of Kalanchoe blossfeldiana (Saniewski et al 2003). However, MJ may also inhibit biosynthesis of anthocyanins, as has been recently found in hypocotyls, but not in cotyledons of young buckwheat seedlings ).…”
Section: Introductionmentioning
confidence: 63%
“…Hence, there is a strong possibility that ethylene is a common factor in the induction of gumming. Saniewski et al (1998b) suggested that jasmonates may also play an important role alongside ethylene in gum formation. Jasmonates, a new group of plant hormones with multiple physiological effects, induce gum formation in tulips (Saniewski et al, 1998a), cherries (Saniewski et al, 2000), peaches (Saniewski et al, 1998b), plums (Saniewski et al, 2004), and apricots (Saniewski et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Saniewski et al (1998b) suggested that jasmonates may also play an important role alongside ethylene in gum formation. Jasmonates, a new group of plant hormones with multiple physiological effects, induce gum formation in tulips (Saniewski et al, 1998a), cherries (Saniewski et al, 2000), peaches (Saniewski et al, 1998b), plums (Saniewski et al, 2004), and apricots (Saniewski et al, 2000). Endogenous jasmonate levels are increased rapidly by many abiotic and biotic kinds of stress observed in ethylene (Saniewski et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation